ANALYSIS OF SEA WATER MASS VARIABILITY IN THE WESTERN NORTH PACIFIC OCEAN ALONG 137Â°E DURING THE PERIOD OF 1972â2022 - Hauna Ahda, Faza
This study examines the variability of seawater mass in the western North Pacific Ocean along the meridian of 137°E over a period spanning 51 years (1972–2022). The research focuses on analyzing the composition and changes in seawater mass during both summer and winter seasons, using data obtained from Japan Meteorological Agency’s CTD measurements. The study identifies and characterizes the North Pacific Intermediate Water (NPIW), one of the major water masses that contains the lowest salinity water column and assesses the interannual and decadal variability. The analysis employs the Optimum Multiparameter (OMP) method and Empirical Orthogonal Function (EOF) to quantify the contributions of different water masses and to identify dominant modes of variability, including the salinity and potensial temperature variability. Findings indicate changes in the vertical profiles of salinity and potential temperature, with notable trends in the shoaling of salinity minimum layers and temperature increases. The study also investigates the influence of ocean-atmosphere interactions, such as the El NiñoSouthern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and Western North Pacific Monsoon (WNPM) on the observed variability, highlighting the critical role these phenomena play in modulating water mass properties in the region. It is found that Kuroshio extension also play role in this interannual and decadal variability. Overall, the results provide valuable insights into the long-term variability of seawater masses in the western North Pacific, contributing to the broader understanding of oceanic processes and their implications for global climate dynamics.